2006
DOI: 10.1002/cbic.200600341
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Relationships between Type I and Type II Iterative Polyketide Synthases: The Aspergillus parasiticus Norsolorinic Acid Synthase

Abstract: Norsolorinic acid synthase (NSAS) is a type I iterative polyketide synthase that occurs in the filamentous fungus Aspergillus parasiticus. PCR was used to clone fragments of NSAS corresponding to the acyl carrier protein (ACP), acyl transferase (AT) and beta-ketoacyl-ACP synthase (KS) catalytic domains. Expression of these gene fragments in Escherichia coli led to the production of soluble ACP and AT proteins. Coexpression of ACP with E. coli holo-ACP synthase (ACPS) let to production of NSAS holo-ACP, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…This in silico approach greatly accelerated efforts to clone and isolate individual domains or combinations of properly folded domains from various fungal polyketide systems for biochemical deconstruction experiments – domain dissection and in vitro reconstitution studies 28-34 . Others have used the sequence conservation of the type II bacterial enzymes or other structurally characterized proteins to successfully select sites at or near predicted domain boundaries for further biochemical interrogation 35-37 .…”
Section: Enzyme Deconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…This in silico approach greatly accelerated efforts to clone and isolate individual domains or combinations of properly folded domains from various fungal polyketide systems for biochemical deconstruction experiments – domain dissection and in vitro reconstitution studies 28-34 . Others have used the sequence conservation of the type II bacterial enzymes or other structurally characterized proteins to successfully select sites at or near predicted domain boundaries for further biochemical interrogation 35-37 .…”
Section: Enzyme Deconstructionmentioning
confidence: 99%
“…Because the SAT 28 and MAT 35 domains load the starter and extender units and the ACP domain carries the elongated intermediates through the catalytic cycle, it was proposed that the KS domain is mostly, if not entirely, responsible for controlling the chain length of the poly-β-keto intermediate 32 . Supporting this notion, the minimal NR-PKS components (KS, MAT, and ACP) from the bikaverin ( 16 ) PKS system (Pks4) primarily produce the correct chain length intermediate but lack the ability to control cyclization chemistry 37 .…”
Section: Control Of Reactive Poly-β-keto Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of natural products derived from these multicatalytic enzymes are the compound classes of the macrolides (e.g., erythromycin) or polyenes (e.g., nystatin). [4] Additionally, iterative type I PKSs are well known from fungi, [5,6] but have also been found in bacteria. [7] In general, all possible intermediates of keto group reductions can be found in type I PKSs.…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial assemblies of heterodomains from a selection of NR-PKSs have shown that polyketide chain length is largely controlled by the β-ketoacyl synthase (KS) domain, and the cyclization pattern is determined by the PT domain(18, 19). The enzyme responsible for the biosynthesis of norsolorinic acid anthrone in Aspergillus parasiticus , the precursor to aflatoxin B 1 ( 1 ), PksA(20), accepts an unusual hexanoyl starter unit from a dedicated pair of yeast-like FASs (HexA/B, Scheme 1A)(2123). The SAT domain of most NR-PKSs prefers acetyl-CoA from common cellular metabolism and shows strong selection against even propionyl-CoA(24).…”
Section: Introductionmentioning
confidence: 99%